1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Induction help

  1. Oct 12, 2009 #1

    I need some help with mathematical induction

    The question is as follows:

    prove that [tex]\sum_{i=0}^n (i-3) \geq \frac{n^2}{4}[/tex]

    I have shown that it holds for the base step where n=12
    [tex]\frac{144}{4} = 36[/tex]
    and the sum of all the i's up to 12 [tex]-3,-2,-1,0,+1,+2,+3,+4,+5,+6,+7,+8,+9 = 39[/tex]


    Now for the inductive step:
    [tex] \sum_{i=0}^{n+1} [/tex]
    and i know this can be rewritten, but im not sure how
    either it's [tex]\sum_{i=0}^{n} (i-3)(i-3)~~ \text{or}~~\sum_{i=0}^{n} (i-3)+(i-3)[/tex]

    How do i proceed from here?
  2. jcsd
  3. Oct 12, 2009 #2


    User Avatar
    Homework Helper

    i think you need
    [tex]\sum_{i=0}^{n+1} (i-3) = ((n+1)-3) + \sum_{i=0}^{n} (i-3)[/tex]

    then assuming the proposition is true for n leads to
    [tex]\sum_{i=0}^{n+1} (i-3) = ((n+1)-3) + \sum_{i=0}^{n} (i-3) \geq ((n+1)-3) + \frac{n^2}{4}[/tex]
  4. Oct 12, 2009 #3


    User Avatar
    Science Advisor

    The last term, that you want to take out of the sum, has i= n+1 so i- 3= n+1-3= n- 2.

    [tex]\sum_{i=0}^{n+1}(i- 3)= \sum_{i=0}^n (i- 3)+ (n+1- 3)= \sum_{i=0}^n (i-3)+ n- 2[/tex]
  5. Oct 12, 2009 #4
    Then you have to add (n+1) to the other side of the equation as well?
    [tex]\sum_{i=0}^n (i-3)+ n- 2 = \frac{(n+1)^2}{4} + (n+1)[/tex]
  6. Oct 12, 2009 #5


    User Avatar
    Science Advisor

    ?? No, add n- 2 to other side as well!!
  7. Oct 14, 2009 #6
    Haha, im so bad at this, it's almost funny :biggrin:
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook